A writing guide for learners of Chinese - Herzberg, Qin Xue; Herzberg, Larry; Dykstra-Pruim, Pennylyn; Redmann, Jennifer (World language writing guides., 2021)
An accessible guide to writing Chinese at the intermediate level.